Membentuk Kemandirian Belajar Melalui Pelatihan Penggunaan Canva Dalam Pembuatan E-Book Sebagai Media Pembelajaran PPKN - Maulana Iman Jaya; Akmaludin Akmaludin; Lukman Sucipto Pratama (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Learning independence is crucial for students to learn autonomously and effectively. This research aims to describe the training on the use of Canva in creating e-books as a learning media for Pendidikan Pancasila dan Kewarganegaraan (PPKn) in the Merdeka Curriculum, with the goal of fostering students' learning independence. The research utilized a qualitative descriptive method with data collection techniques such as observation, interviews, and documentation. The findings indicate that the training on Canva for e-book creation contributes positively to students' learning independence. The training facilitates students in organizing information, expressing ideas, improving graphic design, collaborating, and fostering creativity. Participants acquire knowledge and skills in using Canva as a tool for creating e-books. They learn how to organize content, create appealing layouts, select suitable graphic designs, and effectively integrate text with images. The training also encourages collaboration among students, allowing them to share ideas and work together to achieve better outcomes. The utilization of Canva in e-book creation training proves to be an effective step in cultivating students' learning independence. Through this training, students can develop relevant skills, such as information organization, idea expression, graphic design enhancement, collaboration, and creativity. Therefore, incorporating Canva into PPKn lessons within the Merdeka Curriculum serves as an effective alternative for promoting students' learning independence.